An empirical study of perceived usefulness, ease of use, risks and the intention to use mobile marketing by millennials in Botswana - Shukla, Shuchita (University of the Witwatersrand, Johannesburg, 2024)
The use and impact of mobile marketing platforms have significantly increased in the Botswana market over the last few years, especially during the nationwide lockdown resulting from the COVID-19 pandemic. To better understand this, this research applied the technology acceptance model (TAM) and social penetration theory (SPT) to study the impact of perceived usefulness, ease of use and risks on millennials' intention to use mobile marketing in Botswana. The findings of this study showed that (a) perceived pessimism and privacy issues do not have a negative impact on the final intention to use mobile marketing platforms, while (b) perceived usefulness, ease of use, trust, financial issues and invasiveness does have an impact on the user’s final intention to use mobile marketing platforms. The results of this study offer academic and managerial implications that can contribute to businesses engaged in or intending to engage in mobile marketing strategies
A research report submitted in partial fulfillment of the requirements for the degree of Master of Commerce in Marketing to the Faculty of Commerce, Law and Management, School of Business Science, University of the Witwatersrand, Johannesburg, 2024
Keywords: BOTSWANA; MILLENNIALS; MOBILE MARKETING; PERCEIVED EASE OF USE; SDG-9: Industry, innovation and infrastructure